2014
DOI: 10.1039/c3ta14921h
|View full text |Cite
|
Sign up to set email alerts
|

High sulfur loading composite wrapped by 3D nitrogen-doped graphene as a cathode material for lithium–sulfur batteries

Abstract: A porous three-dimensional nitrogen-doped graphene (3D-NG) was introduced as an interconnected framework for sulfur in lithium-sulfur batteries. The 3D-NG-sulfur composite (3D-NGS) with a high sulfur content of 87.6 wt% was synthesized via a facile one-pot solution method and sulfur was well dispersed within it. The as-designed 3D-NGS composite exhibits excellent rate capability and cyclability.The discharge specific capacity is 792 mA h g À1 after 145 cycles at a current density of 600 mA g À1 and the capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(153 citation statements)
references
References 37 publications
7
145
0
1
Order By: Relevance
“…36 Other studies have also introduced N-doped graphene or porous hollow nanospheres to confine LiPSs. [37][38][39][40] A comprehensive DFT calculation study on pyridinic and quaternary nitrogen doped carbon by Peng et al provides important insights into the underlying mechanism for polysulfide binding ( Figure 3). 41 It was found that the positive Li + ions bind directly to the electron-rich pyridinic nitrogen that possesses a lone electron pair, whereas for the quaternary nitrogen, Li + ions are prone to bind to the neighboring carbon atoms due to the distribution of N-donated electrons in the delocalized π-system.…”
Section: Polar-polar Chemical Interactions With Polysulfidesmentioning
confidence: 99%
“…36 Other studies have also introduced N-doped graphene or porous hollow nanospheres to confine LiPSs. [37][38][39][40] A comprehensive DFT calculation study on pyridinic and quaternary nitrogen doped carbon by Peng et al provides important insights into the underlying mechanism for polysulfide binding ( Figure 3). 41 It was found that the positive Li + ions bind directly to the electron-rich pyridinic nitrogen that possesses a lone electron pair, whereas for the quaternary nitrogen, Li + ions are prone to bind to the neighboring carbon atoms due to the distribution of N-donated electrons in the delocalized π-system.…”
Section: Polar-polar Chemical Interactions With Polysulfidesmentioning
confidence: 99%
“…65 For instance, the most studied material includes N-doped carbon [66][67][68] or graphene, graphene oxides were also highly used to trap dissolved species. [69][70][71][72] In addition to that MXene phases 60 Another issue is rooted from the least sulfur discharge species, Li 2 S. Contrary to the rest of the Li polysulfide species, Li 2 S x (8 > x ≥ 2), Li 2 S is insoluble in aprotic solvents and it is as well electronically insulating which increases the internal resistance of the battery. This increases results in a large polarization that reduces the energy efficiency of the battery.…”
Section: [ ] =mentioning
confidence: 99%
“…In previous work, S-composites with mesoporous activated carbon and conductive polymers with S and S-graphene have been extensively studied, and these systems show relatively high cycle stability. [4][5][6][7] However, these electrodes still have a problem of insufficient charge-discharge efficiency. This is ascribed to the redox shuttle of dissolving Li 2 S n intermediates, and as far as we know, there is no practical method that completely prevents the dissolution of Li 2 S n intermediates with these electrodes.…”
Section: ¹1mentioning
confidence: 99%